Jogo eletrônico, flow e cognição - Piacentini, Mauricio Teixeira (2011)
This research investigates the videogame experience as a synesthetic interaction with an encoded and intentionally proposed world, which produces a specific cognitive impact. Following this path, we initiallly intend to identify some of the characteristics that define the electronic game and its primary coupling interfaces: the hand and the eye, guided by Frank Wilson s research and the concept of technoimages formulated by Vilém Flusser. Then we will consider Mihaly Csíkszentmihályi s theory of optimal experience (flow) and its implications on games. The goal is to understand how play generates knowledge in the body that undergoes experience, and for this we need to define what cognition is, based on theories from three different schools of cognitive science: Cognitivism, Conexionism and Enaction. Finally we will discuss playing as knowing and the role of the game designer as the creator of experiences with cognitive potential